2009
DOI: 10.2174/092986709788803042
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tamoxifen on Immunity

Abstract: Tamoxifen is a widely known anti-estrogen which has been employed in adjuvant treatment of earlystage, estrogen-sensitive breast cancer for over 20 years. Less well known are the effects of tamoxifen on immune function, which we discuss here. We review the growing body of evidence which demonstrates immunomodulatory effects of tamoxifen, including in vitro and in vivo studies as well as observations made in breast cancer patients treated with tamoxifen. Taken together these studies suggest that tamoxifen is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 29 publications
5
95
0
Order By: Relevance
“…ERβ ligands have been proposed as the next-generation estriol treatment, given their protective effect across both sexes [42]. It should be noted that the immunomodulatory effects of tamoxifen may be independent of the estrogen-receptor with its immunomodulation mediated through the multidrug resistance gene product, permeability-glycoprotein [43].…”
Section: Estradiol Synthetic Estrogens and Estriolmentioning
confidence: 99%
“…ERβ ligands have been proposed as the next-generation estriol treatment, given their protective effect across both sexes [42]. It should be noted that the immunomodulatory effects of tamoxifen may be independent of the estrogen-receptor with its immunomodulation mediated through the multidrug resistance gene product, permeability-glycoprotein [43].…”
Section: Estradiol Synthetic Estrogens and Estriolmentioning
confidence: 99%
“…Babina and colleagues reported that tamoxifen is capable of inducing a shift from a cellular (T H 1) to a humoral (T H 2) immunity (19,20). Tamoxifen also induces latent TGFb in breast cancer cell lines (21) and prevents maturation of antigen-presenting cells (22).…”
Section: Introductionmentioning
confidence: 99%
“…The predictive effect of Tregs on chemotherapy response has been demonstrated in a study where the absolute number of Tregs were found to be declined after chemotherapy administration, while the number of cytotoxic T lymphocytes remained stable, resulting in higher rates of pathological complete response in breast cancer patients treated with neoadjuvant cyclophosphamide [20]. Tamoxifen has also shown to have significant effects on immune system functioning [21]. This suggests that biomarkers involved in tumor immune surveillance and tumor immune escape, may also have a predictive effect on endocrine therapy.…”
Section: Predictive Value Of Hla-g In Breast Cancer Patientsmentioning
confidence: 99%